The severity of intermediate penal sanctions: A psychophysical scaling approach for obtaining community perceptions - Harlow, Robert E. (Journal of quantitative criminology, 1995)
The use of intensive supervision programs (ISPs) and other forms of intermediate penal sanctions is increasing in the United States. This paper describes a preliminary investigation of the extent to which informed New Jersey residents believe that intermediate sanctions that are currently being implemented in their state are severe. Using cross-modality matching of magnitude estimation techniques adopted from psychophysics, we obtained severity ratings of 32 sentences across six sentencing modalities (ISPs, probation, imprisonment, home detention, weekend sentencing, and fines) from respondents who had been briefed beforehand about what these sentences entail. Results indicate that our respondents agree that ISPs, weekend sentencing, and home detention have retributive “bite” and may be accepted as sentences in their own right. Probation was seen as being relatively lenient, while imprisonment was seen as highly severe.